Emergence and clonal dissemination of KPC-3-producing Pseudomonas aeruginosa in China with an IncP-2 megaplasmid - Haoyu Ge; Jie Qiao; Jiahao Zheng; Hao Xu; Ruishan Liu; Junhui Zhao; Ruyan Chen; Chenyu Li; Xiaobing Guo; Beiwen Zheng (BMC, 2023)
Abstract Background Despite the global prevalence of Klebsiella pneumoniae Carbapenemase (KPC)-type class A β-lactamases, occurrences of KPC-3-producing isolates in China remain infrequent. This study aims to explore the emergence, antibiotic resistance profiles, and plasmid characteristics of bla KPC-3-carrying Pseudomonas aeruginosa. Methods Species identification was performed by MALDI-TOF-MS, and antimicrobial resistance genes (ARGs) were identified by polymerase chain reaction (PCR). The characteristics of the target strain were detected by whole-genome sequencing (WGS) and antimicrobial susceptibility testing (AST). Plasmids were analyzed by S1-nuclease pulsed-field gel electrophoresis(S1-PFGE), Southern blotting and transconjugation experiment. Results Five P. aeruginosa strains carrying bla KPC-3 were isolated from two Chinese patients without a history of travelling to endemic areas. All strains belonged to the novel sequence type ST1076. The bla KPC-3 was carried on a 395-kb IncP-2 megaplasmid with a conserved structure (IS6100-ISKpn27-bla KPC-3-ISKpn6-korC-klcA), and this genetic sequence was identical to many plasmid-encoded KPC of Pseudomonas species. By further analyzing the genetic context, it was supposed that the original of bla KPC-3 in our work was a series of mutation of bla KPC-2. Conclusions The emergence of a multidrug resistance IncP-2 megaplasmid and clonal transmission of bla KPC-3-producing P. aeruginosa in China underlined the crucial need for continuous monitoring of bla KPC-3 for prevention and control of its further dissemination in China.